Changing Faith : The Dynamics and Consequences of Americans Shifting Religious Identities - Sherkat, Darren E., 1965-; Project Muse. (New York : NYU Press, 2014)
"With analysis spanning across generations and ethnic groups, the volume traces the evolution of the experience of Protestantism and Catholicism in the United States, the dramatic growth of Hinduism, Buddhism, and Islam, and the rise of non-identification, now the second most common religious affiliation in the country. Drawing on that wealth of data, it details the impact of religious commitments on broad arenas of American social life, including family and sexuality, economic well-being, political commitments, and social values. Exploring religious change among those of European heritage as well as of Eastern and Western European immigrants, African Americans, Asians, Latin Americans, and Native Americans, Changing Faith not only provides a comprehensive and ethnically inclusive demographic overview of the juncture between religion and ethnicity within both the private and public sphere, but also brings empirical analysis back to the sociology of religion."--Publisher's Web site.
Cover; Contents; Acknowledgments; Introduction: Making Sense of American Religion; 1 Religious Identification in America; 2 Religious Switching and Religious Change; 3 Belonging and Believing; 4 Faith, Family, and Fortune; 5 Religious Identification and Politics in the United States; Conclusions: Making Sense of Shifting Identities and Their Influence; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; About the Author.
Text in English.
Description based on print version record.
Keywords: Identification (Religion); Religion and sociology; RELIGION -- General; RELIGION -- Reference; RELIGION -- Essays; RELIGION -- Comparative Religion; Sociologie religieuse -- États-Unis.; Identification (Religion); Religion and sociology -- United States; Identification (Religion); United States; Electronic books